Incidence of puerperal infection cases in a reference maternity in the municipality of Teresina-PI (Research, Society and Development, 2022)
Objective: to analyze the incidence of cases of puerperal infection in a reference maternity hospital in the city of Teresina-PI. Results: During 2020, the predominant infections in the Maternal ICU were Primary Laboratory Bloodstream Infection (IPCSL), Urinary Tract Infection (UTI) and Surgical Site Infection (ISC), respectively. In contrast, in 2021, the incidence of IPCSL and UTI remained in the same sequence. In the year 2021, within the context of surgical site infection, the most incident microorganisms were mostly E. Coli, S.Aureus, K. Pneumoniae respectively. Conclusion: The pandemic context influenced the increase in the number of patients, mainly with Surgical Site Infection (SSI), in which the significant increase ratified the importance of research on the incidence of puerperal infections, since, in order to reduce morbidity and mortality maternal and neonatal most causes can be avoided, and attention should be paid to care based on prophylactic measures.